Cationic Exciplexes: Role of Hydrogen Bonding in Deactivation and Electronic Coupling. Issue 17 (9th July 2021) - Dinnocenzo, Joseph P.; Farid, Samir
Abstract: Emissive properties for the cationic exciplex (A + */D→A . D .+ ) of an isoquinolinium cation tethered to a substituted arene (1 + ) are strongly affected by hydrogen bonding solvents. At equal dielectric constant ( ϵ ), the ground‐to‐excited state energy gaps (Δ G ) and solvent reorganization energies ( λ s ) decrease from nitriles to aliphatic alcohols. The corresponding decrease from aliphatic alcohols to high hydrogen bond acidity solvents is ∼3 times larger. The exciplex decay ( k Ex ), largely determined by unfolding of the exciplex to a stretched conformer, changes in a complex way depending on the strength of the hydrogen bond ability of these solvents. In contrast, the electronic couplings between the exciplex ground, excited, and charge transfer states do not show a solvent functionality dependence. Abstract : Hydrogen bonding to cationic exciplexes affects the rate constants for exciplex decay ( k EX ) in a complex way depending on the hydrogen bond donor ability of the solvent. Hydrogen bonding decreases the ground to excited state energy gaps and solvent reorganization energies, but increases the vibrational reorganization energies. In contrast, the electronic couplings between the exciplex ground, excited, and charge transfer states do not show a solvent functionality dependence.